ASEAN-EU university network programme on EMC and SI education - F.G. Canavero; C. Christopoulos; H. Grabinski; None See Kye Yak; W. Khan-ngern (My University, 2005)
This paper reports about a project for the creation of an innovative university course devoted to the preparation of future electronic designers to the challenges imposed by the assurance of the electrical performance of high-speed electronic systems. The target groups are future university teaching staff and future electronic systems designers. Activities are developed by means of sharing research results, seminars, experience exchange and the development of demonstrators to be used for teaching. The partnership is composed by Technical University of Turin (Italy), University of Hannover (Germany), University of Nottingham (UK), Nanyang Technological University (Singapore) and King Monguts Institute of Technology Lad-krabang, Bangkok (Thailand). The program is partially funded by the European Commission under the ASEAN-EU University Network Programme (AUNP) and its duration is 24 months.
Keywords: European commission; Technical university; Research centre; Experimental Learning in Engineering